Resisting the Stigma of Being Papuan - Indonesia, Alfath Bagus Panuntun El Nur; Ramadhan, Gilang (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
This article shows the stigmatization of Papuan youth in the Special Region of Yogyakarta (DIY). The Papuan youth in this research is represented by a youth organization called The Mappi and Puncak Griya Sekar Aji Family Association (Ikatan Keluarga Mappi dan Puncak Griya Sekar Aji - IKMP GSA), which has made extensive efforts to create a unique identity of the indigenous people of Papua or Orang Asli Papua (OAPs) through various initiatives, such as social contributions and participation in popular culture. This study’s extensive ethnographic data over four years revealed that OAPs gradually deconstruct the prevailing negative stereotypes attached to Papuan students in DIY. The success could be attributed to OAPs’ collective efforts in establishing and running IKMP GSA. The members also exhibit a high level of self-awareness and actively participate in social activities and mainstream cultural elements in their daily lives. The results provide empirical evidence of effective, repeatable strategies to help improve Papuan students’ social lives across Indonesia.